Effect of Stocking Density on Growth and Survival Rate of Giant Gouramy (Osphrenemus gouramy Lac.) Seed - S. Sarah; . Widanarni; Agus Oman Sudrajat (Jurnal Akuakultur Indonesia)
This experiment was conducted to study the stocking density effect on growth and survival rate of giant gouramy seed in the aquarium. Fish were stocked at the density of 2.5; 5.0; 7.5 and 10 individual/l with average initial weight and length were 0.013 g and 5.56 mm, respectively. Fish were fed with silkworm (Tubifex sp.) ad libitum in the morning and evening for 22 days of experiment. Aquarium was siphoned and water was changed everyday for maintaining good water quality. Result showed that survival rate remain high in all treatment (93.5 - 95.5%). Increasing stocking density from 2.5 to 10 individual/I did not affect survival rate. On the other hand growth rate and feed efficiency decreased, while fish yield increased. Stocking density of 2,5 individual/l gave  the highest daily growth rate, individual growth rate, growth in length and feed efficiency of 12.94%, 0.0081 g/day, 16.84 mm and 12.51%; respectively. The highest value for fish yield (0,0360 g/l/day) was obtained from stocking density of 10 individual/l